Evolutionary Insights Into Two Widespread Ectomycorrhizal Fungi (Pisolithus) From Comparative Analysis of Mitochondrial Genomes - Wu, Peng; Yao, Tian; Ren, Yuanhang; Ye, Jinghua; Qing, Yuan; Li, Qiang; Gui, Mingying (Frontiers in Microbiology, 2021)
The genus Pisolithus is a group of global ectomycorrhizal fungi. The characterizations of Pisolithus mitochondrial genomes have still been unknown. In the present study, the complete mitogenomes of two Pisolithus species, P. microcarpus, and P. tinctorius, were assembled and compared with other Boletales mitogenomes. Both Pisolithus mitogenomes comprised circular DNA molecules with sizes of 43,990 bp and 44,054 bp, respectively. Comparative mitogenomic analysis showed that the rps3 gene differentiated greatly between Boletales species, and this gene may be subjected to strong pressure of positive selection between some Boletales species. Several plasmid-derived genes and genes with unknown functions were detected in the two Pisolithus mitogenomes, which needs further analysis. The two Pisolithus species show a high degree of collinearity, which may represent the gene arrangement of the ancestors of ectomycorrhizal Boletales species. Frequent intron loss/gain events were detected in Boletales and basidiomycetes, and intron P717 was only detected in P. tinctorius out of the eight Boletales mitogenomes tested. We reconstructed phylogeny of 79 basidiomycetes based on combined mitochondrial gene dataset, and obtained well-supported phylogenetic topologies. This study served as the first report on the mitogenomes of the family Pisolithaceae, which will promote the understanding of the evolution of Pisolithus species.